(untitled) (Bangladesh Journal of Medical Science, 2025)
Introduction Neurological harmmay be a basic complication related with surgical expulsion of affected mandibular third molars. Such wounds can happen specifically or in a roundabout way, emphasizing the significance of surveying the peril of post-operative second rate alveolar nerve (IAN) damage. The preoperative arranging included analyzing advanced radiographs utilizing Rood and Shehab classification, comprising different radiographic signs. We utilize Rood and Shehab’s classification on this consider to get to the plausibility of nerve damage. We exhort for more symptomatic degree. Methodology The research employed a retrospective cross-sectional study design. A sum of 1298 participants were included in the study, conducted in the Qassim Province. Inclusion criteria specified patients with impacted mandibular third molars. Data was analyzed using the SPSS program. Results Among the surveyed participants, three prevalent conditions stood out prominently; canal narrowing (946, 73.8%), canal deflection (935, 73.0%), and canal darkening (684, 53.4%). Conversely, lower occurrences were noted for dark and canal apex bifid (15, 1.2%), canal diversion (2, 0.2%), and canal narrowing (56, 4.4%). Interruption of the white streak was observed in approximately one- third of the cases (412, 32.2%). Conclusion The high prevalence of narrowing, deflection, and darkening of the root underscores the clinical significance of these conditions, necessitating careful consideration in diagnostic assessments. BJMS, Volume: 24. Supplementary Issue 2025, Page : 117-122